Bicomplex Green's theorem and its application - Goswami, Mahesh Puri; Kumar, Raj (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We consider a bicomplex extension of Green's theorem, which is a key result in the integral calculus. By its application, we illustrate the bicomplex Cauchy–Goursat theorem and employ the bicomplex version of Green's theorem in order to efficiently determine numerous integrals involving various forms of bicomplex functions.